Experimental verification of three-dimensional numerical calculations of radial fans - Piwowarski, Marian; Ziemiański, Paweł; Mioduszewski, Piotr; Czyżewicz, Jacek; Bortkiewicz, Mateusz; Laszuk , Krzysztof; Madej, Krzysztof; Cybulski, Karol; Naumczyk , Tomasz; Fabiański, Tomasz; Makara, Adam; Jaskólska , Julia; et al. (Instal, 2026)
The article presents the results of experimental verification of three-dimensional CFD (Computational Fluid Dynamics) calculations for radial fans, carried out as part of the COLUBRIS research project at Nyborg-Mawent. The calculations were performed in ANSYS CFX 3D for viscous and compressible flow using the k-ω SST turbulence model. The analyses were performed for a complete geometric model (suction nozzle, impeller, casing, outlet) at a rotational speed of 2950 rpm and a flow range of 0.4–1.2 m3/s, corresponding to total pressure values of 1.5–3.8 kPa. The CFD results were compared with laboratory measurements performed on an actual test bench. A very good quantitative and qualitative agreement was obtained – the maximum differences were up to 3.5% for efficiency, 3.1% for total pressure, and 2.2% for power. The largest discrepancies occurred at extreme flow rates (below 0.5 m3/s and above 1.1 m3/s), which was attributed to separation and recirculation phenomena in the diffuser duct. The results obtained confirm the reliability of the methodology and the usefulness of 3D models for the design and further optimization of radial fans, including the identification of areas generating flow and acoustic losses.